2012
DOI: 10.1258/jtt.2012.gth105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of type 2 diabetes behavioural telehealth interventions on glycaemic control and adherence: a systematic review

Abstract: We reviewed the effect of behavioural telehealth interventions on glycaemic control and diabetes self-management in patients with type 2 diabetes. The databases CINAHL, Medline and psychINFO were searched in August 2012. Journal articles were selected that had been published in English with a randomized controlled trial design using a usual care comparison group, and in which the primary intervention component was delivered by telehealth. Relevant outcome measures were glycaemic control and one or more of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 26 publications
2
64
0
Order By: Relevance
“…In the outpatient setting, technology-assisted interventions have been used to enhance the efficiency of care delivery, to remind patients of appointments, to monitor disease status at home, and to increase healthpromoting behaviors [11][12][13]. Technologies, including interactive voice response systems (IVR), could efficiently conduct proactive monitoring, thereby reducing effort required by nurse coaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the outpatient setting, technology-assisted interventions have been used to enhance the efficiency of care delivery, to remind patients of appointments, to monitor disease status at home, and to increase healthpromoting behaviors [11][12][13]. Technologies, including interactive voice response systems (IVR), could efficiently conduct proactive monitoring, thereby reducing effort required by nurse coaches.…”
Section: Introductionmentioning
confidence: 99%
“…Telephone-delivered interventions are increasingly being investigated as they have the potential for broad population reach, and for delivering the repeated contacts necessary to promote maintenance of behavior change and related clinical improvements (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The interventions evaluated involved remote monitoring and transmission of physiological data, assessment of health symptoms, facilitation of contact with a health care professional via telephone or video, disease-specific education, and reinforcement of self-management behaviors. Six reviews identified the effectiveness of telehealth interventions for chronic obstructive pulmonary disease (COPD) (85,99), chronic heart failure (65, 100, 104), and diabetes (21), as compared to usual care. One review found over three-quarters of studies (76%) reported positive effects of telemedicine interventions across a number of chronic conditions (asthma, COPD, heart failure, hypertension, and diabetes) (135).…”
Section: Evidence For Effectiveness Uptake and Use Of Technology Inmentioning
confidence: 99%
“…One review found over three-quarters of studies (76%) reported positive effects of telemedicine interventions across a number of chronic conditions (asthma, COPD, heart failure, hypertension, and diabetes) (135). Six reviews reported reduced rates of mortality (65,85) and hospitalizations (28,65,85,99,100); reduced BMI and weight (21); increased smoking cessation, medication adherence, and BG self-monitoring (21); and improvements in glycemic control for individuals with type 2 diabetes and across several self-care behaviors, including physical activity and diet (21). Increased quality of life was reported in 66% (seven of nine reviews) of the reviews (28,65,85,99,100,125).…”
Section: Evidence For Effectiveness Uptake and Use Of Technology Inmentioning
confidence: 99%
See 1 more Smart Citation